2020
DOI: 10.24875/bmhim.20000265
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of a pediatric hospital in the face of the COVID-19 pandemic

Abstract: Actions of the Hospital Infantil de México Federico Gómez in response to the pandemicSince the beginning of 2020, Mexico has been preparing for the COVID-19 pandemic. One of the measures was the restructuring of hospitals. The Hospital Infantil de México Federico Gómez (HIMFG) was designated as a COVID-19 hospital for the pediatric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The study was done at a Pediatric Tertiary Level Referral Hospital restructured to receive COVID patients in Mexico City between April 2020 and December 2021 (6). Newborns with a positive real time polymerase chain reaction (RT-PCR) for the SARS-CoV-2 virus by nasal swab irrespective of the working diagnosis were included.…”
Section: Methodsmentioning
confidence: 99%
“…The study was done at a Pediatric Tertiary Level Referral Hospital restructured to receive COVID patients in Mexico City between April 2020 and December 2021 (6). Newborns with a positive real time polymerase chain reaction (RT-PCR) for the SARS-CoV-2 virus by nasal swab irrespective of the working diagnosis were included.…”
Section: Methodsmentioning
confidence: 99%
“…At the beginning of the COVID-19 pandemic, the hospital was restructured to be able to have COVID areas as well as to trace both positive cases and contacts. Villa-Guillén et al reported the restructuring of the hospital, in which it is mentioned that three COVID areas were established ( 11 ). The first area is for general pediatric care, the second for pediatric intensive care, and the third for neonatal intensive care.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to mention that these areas do not have individual rooms and the beds are not divided from one another. The ventilation of these areas is natural and air extractors were placed ( 19 ). Visitors' access to these areas was restricted from April to June 2020; which was period 1 of the study.…”
Section: Methodsmentioning
confidence: 99%